Effects of Intraoperative Dexmedetomidine on Postoperative Pain in Highly Nicotine-Dependent Patients After Thoracic Surgery: A Prospective, Randomized, Controlled Trial. Issue 22 (May 2016) - Cai, Xingzhi; Zhang, Ping; Lu, Sufen; Zhang, Zongwang; Yu, Ailan; Liu, Donghua; Wu, Shanshan
Abstract : Abstract: To investigate the effects of intraoperative dexmedetomidine on pain in highly nicotine-dependent patients after thoracic surgery. Highly nicotine-dependent men underwent thoracic surgery and received postoperative patient-controlled intravenous analgesia with sufentanil. In dexmedetomidine group (experimental group, n = 46), dexmedetomidine was given at a loading dose of 1 μg/kg for 10 minutes, followed by continuous infusion at 0.5 μg/kg/h until 30 minutes before the end of surgery. The saline group (control group, n = 48) received the same volume of saline. General anesthesia was administered via a combination of inhalation and intravenous anesthetics. If necessary, patients were administered a loading dose of sufentanil by an anesthesiologist immediately after surgery (0 hours). Patient-controlled analgesia was started when the patient's resting numerical rating scale (NRS) score was less than 4. Resting and coughing NRS scores and sufentanil dosage were recorded 0, 1, 4 hours, and every 4 hours until 48 hours after surgery. Dosages of other rescue analgesics were converted to the sufentanil dosage. Surgical data, adverse effects, and degree of satisfaction were obtained. Cumulative sufentanil dosage, resting NRS, and coughing NRS in the first 24 hours after surgery and heart rate were lower in the experimental compared with the control group ( P <0.05). No patient experienced sedation or respiratory depression. Frequency of nausea and vomiting and degree of satisfaction were similar in both groups. Intraoperative dexmedetomidine was associated with reduced resting and coughing NRS scores and a sufentanil-sparing effect during the first 24 hours after thoracic surgery.